A framework of urban entrepreneurship for women breadwinners. Issue 5 (13th July 2021) - Ziyae, Babak; Sadeghi, Hossein; Shahamat Nejad, Mina; Tajpour, Mehdi
Abstract : Purpose: Today, urban entrepreneurship is considered one of the vital strategies that directed cities toward self-control by reducing the unemployment rate and its arising problems, creating sustainable revenue and preparing the ground for citizens' independence. This paper aims to present an integrated foresight framework and establish the boundary conditions for urban entrepreneurship of women breadwinners. The study explains how particular women solve workplace-specific poverty and foster urban wealth by developing startups, new businesses or ventures. Design/methodology/approach: The current research uses a qualitative method and uses the grounded theory approach. Data were collected by selecting 24 outstanding women entrepreneurs using snowball sampling and semi-structured interviews in Tehran Metropolitan. Findings: The results of the study reveal that the main aspects of the model of urban entrepreneurship consist of causal factors, intervening factors and contextual conditions. By shaping the policies and organizing educational plans, training courses and empowering of women, as well as the establishment of supportive units for the development, identification of the opportunities, developing protective rules, the factors as mentioned above lead to cultural, social and economic development, tendency toward entrepreneurship and development of entrepreneurship among women. Originality/value: This study undertakes a first of its kind cross-disciplinary conceptual analysis at the level of how women breadwinners foster urban wealth using developing new businesses, startups or ventures. Despite the importance of urban entrepreneurship, theories for understanding the nexus of urban contexts remain underdeveloped. Therefore, there is still a theoretical gap and lack of research; hence, the current study tries to shed light on the topic and fill this gap in the body of knowledge.